Kinematic analysis of robotic bevel-gear trains: An application of network model approach - Uyguroglu, M; Tokad, Y (Springer, 1998)
The network model approach for rigid and multi-rigid body systems developed recently [1,2] can also be used conveniently in formulating system equations or equations of motion of three-dimensional mechanical systems of interconnected rigid bodies. In this article, this method is further elaborated for establishing only the kinematics of spatial robotic bevel-gear trains. However the dynamic analysis of such systems using the same method is also possible and will be taken up in a future publication.
Keywords: bendix wrist mechanism; network model; three-dimensional mechanical system; kinematics